PELATIHAN PENGEMBANGAN PEMBELAJARAN DENGAN LEARNING MANAGEMENT SYSTEM DAN EXAM VIEW BAGI GURU SMPN 2 SUNGAILIAT - Agita Rindri, Yang; Silalahi, Parulian; Andriyanto, Sidhiq; Fadlilah, Husnul; Pidaryani, Pidaryani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Information and Communication Technology (ICT) has a very important role in the world of education. Apart from being used as educational infrastructure, ICT can be used as a learning tool and facility so that it can provide alternative learning experiences that are more innovative, efficient, and enjoyable if used properly. One of the implementations of ICT in the world of education is the use of the Learning Management System (LMS) and Examview which can be used to help manage online-based learning. This Community Service aims to provide training to teachers at SMP Negeri 2 Sungailiat in using LMS and Examview as an effort to improve Information and Communication Technology (ICT) skills for SMP Negeri 2 Sungailiat teachers in the current era of digitalization. The service methods carried out include: 1) Designing and creating an LMS for SMP Negeri 2 Sungailiat, 2) Providing training on LMS management and using Examview for 3 days, and 3) Assisting teachers in managing the LMS. The result of this Community Service activity is an increase in teacher skills in managing learning using LMS and Examview as shown by the results of the observation that has been carried out. From the observation results, it was found that there was an increase in teacher skills in developing learning with LMS and Examview. Eighty Percent (80%) of teachers had succeeded in developing learning in the LMS that had been provided by the team and used the LMS to help the learning process at SMPN 2 Sungailiat.